2006
DOI: 10.1002/joc.1378
|View full text |Cite
|
Sign up to set email alerts
|

How well do the central England temperature and the England and Wales precipitation series represent the climate of the UK?

Abstract: In this paper we compare the Central England Temperature (CET) and England and Wales Precipitation (EWP) series with temperature and precipitation records from 24 individual meteorological stations throughout the UK over a 41-year period 1964-2004. With a single exception, the correlation of CET monthly means with those of all local stations was highly significant (p < 0.001). Correlations with EWP were not as large, but for the most part were highly significant; exceptions occurring increasingly in the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Previous researchers have shown that CET data are representative of the UK as a whole (Croxton et al . ), and paired monthly correlations between the regional and CET data for the years between 1910 and 1981 (encompassing the overlap in CET and regional temperature data for all years of NHM specimen collection) justify this conclusion (all Pearson's correlations > 0·96). In addition, pairwise comparisons of mean monthly air temperatures between the two record types are not significantly different (Wilcoxon signed‐rank test; P > 0·05), except for August temperatures ( P = 0·02) where the regional data are warmer than CET data by 0·42 °C on average.…”
Section: Methodsmentioning
confidence: 83%
“…Previous researchers have shown that CET data are representative of the UK as a whole (Croxton et al . ), and paired monthly correlations between the regional and CET data for the years between 1910 and 1981 (encompassing the overlap in CET and regional temperature data for all years of NHM specimen collection) justify this conclusion (all Pearson's correlations > 0·96). In addition, pairwise comparisons of mean monthly air temperatures between the two record types are not significantly different (Wilcoxon signed‐rank test; P > 0·05), except for August temperatures ( P = 0·02) where the regional data are warmer than CET data by 0·42 °C on average.…”
Section: Methodsmentioning
confidence: 83%
“…Monthly mean EWP starts in 1766 and is representative of the land area of England and Wales. Both CET and EWP have been shown to be representative of the UK climate with CET having larger spatial correlations than EWP, but even the latter was highly representative for the most part (Jones and Hulme, 1997;Croxton et al, 2006). Given the length of these two records, it is possible to estimate an approximation of 'natural' climate variability.…”
Section: Methodsmentioning
confidence: 99%
“…html). Because the Welsh site is close to the western coast of the UK, the Central England record may not be representative here, particularly in winter (Croxton et al 2006). Consequently, we obtained temperature data from Aberporth meteorological station (ca.…”
Section: First Observation Dates Of Spawning By Common Frogmentioning
confidence: 99%